2014
DOI: 10.3892/ol.2014.2132
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma metastatic to the cervical spine causing a C6 compression fracture: A case report

Abstract: Leiomyosarcoma is a rare malignant tumor derived from smooth muscle cells, which commonly metastasizes to the lungs, liver, kidney, brain and skin. The current study presents the case of a 42-year-old male who presented with progressive neck pain and numbness of the left arm. Spinal computed tomography and magnetic resonance imaging revealed osteolytic lesions of numerous vertebrae (C2, C3, C4, C5, C6, C7, T1 and T2). With regard to the C6 vertebra, total destruction of the vertebral body resulted in vertebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Sun et al, in 2013, reported a metastatic LMS lesion to the cervical spine with destruction of the C6 vertebra; the patient underwent an anterior decompression and fusion. [8] In 2022, LiBrizzi et al retrospectively analyzed bone metastases in LMS patients; most involved the femur, humerus, and spine; the latter were typically managed with kyphoplasty, decompression alone, and/or decompression and fusion. [4] Survival rates for spinal LMS LMS are aggressive, highly malignant lesions that frequently recur and metastasize.…”
Section: Lms Rarely Metastasizes To the Spinementioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al, in 2013, reported a metastatic LMS lesion to the cervical spine with destruction of the C6 vertebra; the patient underwent an anterior decompression and fusion. [8] In 2022, LiBrizzi et al retrospectively analyzed bone metastases in LMS patients; most involved the femur, humerus, and spine; the latter were typically managed with kyphoplasty, decompression alone, and/or decompression and fusion. [4] Survival rates for spinal LMS LMS are aggressive, highly malignant lesions that frequently recur and metastasize.…”
Section: Lms Rarely Metastasizes To the Spinementioning
confidence: 99%
“…[ 2 ] Metastatic LMS spinal lesions classically have a poor prognosis due to the high risk for tumor recurrence and relative resistance to radiation and/or chemotherapy. [ 8 ] Here, a 63-year-old female who, in 2021, had a retroperitoneal LMS resected newly presented with a right C5 level hemiparesis attributed to a C5 laminar/C5–C6 bony foraminal lesion. Following resection, the lesion proved to be a LMS metastasis that recurred within one year following gross total tumor removal despite adjuvant oncologic treatment.…”
Section: Introductionmentioning
confidence: 99%